Formulation of Wound Healing Hydrogel from 70% Ethanol Extract of Kelakai Roots (Stenochlaena palustris (Burm. F.) Bedd) with Polymer Combination of PVA/HPMC - Forestryana, Dyera; Pebrianie, Shilpa; Ramadhan, Hafiz; Restapaty, Ratna (Sanata Dharma University, 2024)
Kelakai root contains alkaloids, saponins, tannins, and flavonoids. This compound is known to have medicinal properties such as wound healing. The effectiveness of wound healing increased by using hydrogel to deliver the active substance. The use of polymers played a role in delivering the active substance. This study aimed to formulate hydrogels for wound healing with various concentrations of polyvinyl alcohol (PVA) and hydroxy propyl methyl cellulose (HPMC) K4M. Preparation of hydrogel by the solvent casting method used 0.2% Kelakai root extract. The physical characteristics of hydrogel investigated before and after the stability test included organoleptic, weight uniformity, thickness, pH, moisture content, and hedonic test of Kelakai roots extract hydrogel. The optimum formula was tested for wound healing activity. The data obtained were then analyzed using Wilcoxon testswith p0.05 considered significant. Physically, Kelakai root extract hydrogel met the test requirements. The results of the wound-healing activity showed that the hydrogel extract of the Kelakai root was able to heal the wounds within seven days. There was a significant difference in wound healing time with p=0.014. The optimum formula obtained based on the stability test was F4 with a 1:4 ratio of PVA and HPMC.